Pneumo-mediastinum, pneumoperitoneum, and pneumo-scrotum with extensive increasing subcutaneous emphysema: a rare presentation of colonic perforation - Kulbhushan Haldeniya; S. R. Krishna; Annagiri Raghavendra; Pawan Kumar Singh (Egyptian Liver Journal, 2023)
Abstract Background Colonic perforation usually presents with classical signs of peritonitis. However, isolated retroperitoneal colonic perforation can present with varied clinical signs and symptoms and pose diagnostic challenges. Pneumo-mediastinum and abdominal subcutaneous emphysema can be one of the presenting signs of colonic perforation. Case report A 33-year-old male presented with abdominal distension and extensive subcutaneous emphysema over the abdomen, pneumo-mediastinum, and pneumo-scrotum secondary to sigmoid colon perforation from a foreign body. The patient did not have classical signs of peritonitis. Conclusion Being vigilant about the potential of colonic perforation is crucial when observing a significantly increasing subcutaneous emphysema across different parts of the body. Attending clinicians should always keep intraabdominal pathology in mind when a direct cause for these symptoms cannot be found and the patient’s symptoms become progressive.